Effects of process parameters on the formability of sheet metal during plastic injection forming - ŞEN, MURAT (CARL HANSER VERLAG, 2020)
Plastic injection forming (PIF) is an alternative sheet metal forming method for complex geometrical parts with dimensions in low tolerance. This method is a combination of injection molding and hydroforming in which a molten polymer material has been injected over a sheet metal via a plastic injection molding machine. In this study, aluminum sheets 1.5 mm thick were shaped by PIF at various injection pressures, melt temperatures and injection speed. The effects of these parameters on the formability of the sheet metal. were investigated using the experimental design technique. The thinning rate, flange radius and the hardness values of the shaped sheets were considered in the experimental study. Injection pressure was found to be the most effective parameter and melt temperature was the second degree effective parameter for the thinning rate. The usability of the PIF process in industrial applications as an alternative method was emphasized by comparing PIF with conventional hydroforming by means of the finite element method (Ls-Dyna). A 2.07 % deviation was observed between the FE results for hydroforming and the experimental results for PIF.
Keywords: Plastic injection forming; thinning rate; hydroforming; finite element method; Taguchi; formability; BLANK-HOLDER FORCE; DEEP-DRAWING PROCESS; FINITE-ELEMENT-ANALYSIS; SIMULATION; VARIABLES